Biosynthesis Of Silver Nanoparticles From Foeniculum Vulgare Leaf Extract For Antimicrobial And Antioxidant Activities - Fasika Dereje (ASTU, 2022)
Ethiopian Medicinal Plant, Foeniculum Vulgare Leaf Mediated Green Silver Nanoparticles Were Successfully Synthesized For The First Time. In This Study, Silver Nanoparticles Were Biosynthesized By Using The Leaf Extracts Of Foeniculum Vulgare And 0.1 M Of Silver Nitrate In Three Different Volume Ratios Of 100 Ml:100 Ml (1:1), 50 Ml:150 Ml (1:3), And 150 Ml:50ml (3:1). The Biosynthesized Silver Nanoparticles Were Characterized By Xrd, Uv-Vis, Ftir,And Sem. The Xrd Results Confirmed That Silver Nanoparticles Were Found To Exhibit A Face Centered Cubic Phase Structure And The Sharp And Intense Peaks At 2?? Values Of 38.21??, 44.38??,64.77??, And 77.58?? Have Confirmed The Formation Of Crystalline Silver Nanoparticles. The Band Gap Energy Of Biosynthesized Silver Nanoparticles Was Found To Be 3.23 Ev, 3.35 Ev, And 3.51ev For 1:1, 1:3, And 3:1 Ratios Respectively. Ft-Ir Spectra Were Recorded For The Foeniculum Vulgare Leaf Extract And For The Silver Nanoparticles To Identify The Biomolecules Involved In The Synthesis Process. The Sem Images Showed A Spherical Shape For Silver Nanoparticles. The Antimicrobial Activity Of The Biosynthesized Silver Nanoparticles Was Screened Against Two Gram-Positive Bacteria (Streptococcus Pyogenes And Staphylococcus Aureus) And Two Gram Negative Bacteria (Escherichia Coli And Pseudomonas Aeruginosa) And Fungal Strains (Aspergillus Niger And Candida Albicans) Using The Using Agar Disc Diffusion Method. Results Showed That All The Studied Silver Nanoparticles Ratios Displayed Good Antibacterial Activity Compared To Amoxicillin Which Was Used As A Positive Control. Among The Three Different Volume Ratios, Silver Nanoparticles 3:1 Ratios Shows Better Performance Towards Gram Positive Bacteria, Due To Its Smaller Average Crystalline Size And Uniform Morphology Observed In The Sem Image Relative To The Other Two Ratios Of Silver Nanoparticles. The Best Antifungal Activity Was Displayed By Aspergillus Niger At A 3:1 Ratio With A Maximum Zone Of Inhibition Of 13, 14.8, And 16.8 Mm At The Concentrations Of 15, 20, And 25 Mg/Ml, Respectively. The Antioxidant Capacity Of Silver Nanoparticles Was Investigated In Vitro By 2, 2-Diphenyl-1-Picrylhydrazyl (Dpph) Assays. Dpph Radical Scavenging Activity Displayed 42.4%, 27.3%, And 28.9% Inhibition For 1:1, 1:3 And 3:1 Silver Nanoparticles Volume Ratios Respectively, At 800 ??G/Ml.
Keywords: Antimicrobial Activity, Antioxidant, Foeniculum Vulgare, And Silver Nanoparticles